Fetomaternal outcome in post dated pregnancy - Kandalgaonkar, Vishakha Prakash; Kose, Varsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The risks to the fetus increase after 41 weeks mainly due to increasing fetal weight, decline in placental function, oligohydramnios which increase chances of cord compression, and meconium aspiration. Perinatal mortality after 42 weeks is twice as compared to the perinatal mortality at 40 weeks and by 44 weeks the rate is increased up to threefold. In cases of prolonged pregnancy, fetus is more at risk of hypoxia during labor than a fetus at term. Methods: This cross sectional observational study of feto-maternal outcome in post dated pregnancy (Women beyond 40 weeks of gestation) was carried out in the department of obstetrics and gynaecology in a rural based tertiary care centre from October 2016 to September 2018, willing to participate and fulfilling the inclusion and exclusion criteria in the study period. Results: Majority i.e. 45 patients (46.9%) went into spontaneous labour and delivered vaginally, whereas 16 patients (16.7%) required caesarean section. Among all 45 participants who were given induction, maximum 26 (57.78%) were induced by Dinoprostone gel, 4 patients (8.89%) were induced by Tab. Misoprostol. Conclusions: The present study, we conclude that, the post dated pregnancy can be considered as a high risk factor from the point of view of fetal outcome as there is more fetal morbidity.